2018
DOI: 10.7554/elife.38111
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A localises to mitochondria to control organelle dynamics and energy production

Abstract: Many epithelial cancers show cell cycle dysfunction tightly correlated with the overexpression of the serine/threonine kinase Aurora A (AURKA). Its role in mitotic progression has been extensively characterised, and evidence for new AURKA functions emerges. Here, we reveal that AURKA is located and imported in mitochondria in several human cancer cell lines. Mitochondrial AURKA impacts on two organelle functions: mitochondrial dynamics and energy production. When AURKA is expressed at endogenous levels during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
133
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(165 citation statements)
references
References 53 publications
12
133
2
1
Order By: Relevance
“…Horn and co-authors had identified the fission factor dynamin-related protein-1 (DRP1) as the target of FZR1 required for its effect on mitochondrial morphology [43]. Here we found that inhibition of AURKA activity completely rescued mitochondrial length and morphology in FZR1 KO cells ( Figure 5E,F), consistent with data showing AURKA to be an upstream regulator of DRP1 [11,13]. Treatment of FZR1 KO cells with an AURKB-specific inhibitor had no effect on mitochondrial length (Supplementary Figure S4).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Horn and co-authors had identified the fission factor dynamin-related protein-1 (DRP1) as the target of FZR1 required for its effect on mitochondrial morphology [43]. Here we found that inhibition of AURKA activity completely rescued mitochondrial length and morphology in FZR1 KO cells ( Figure 5E,F), consistent with data showing AURKA to be an upstream regulator of DRP1 [11,13]. Treatment of FZR1 KO cells with an AURKB-specific inhibitor had no effect on mitochondrial length (Supplementary Figure S4).…”
Section: Resultssupporting
confidence: 89%
“…Next, we explored how FZR1 affects known AURKA functions in interphase. We and others have previously described a role for AURKA, at physiologically relevant levels of expression, in promoting mitochondrial fission during interphase [11,12], an observation thought to be significant to cellular metabolism given the intimate link between mitochondrial morphology and function [42]. We hypothesized therefore that one consequence of increased interphase AURKA activity should be increased mitochondrial fragmentation in FZR1 KO cells, and indeed mitochondrial fragmentation following FZR1 siRNA treatment of HeLa cells has previously been described [43].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…AURKA was first described to be a mitotic protein with multiple partners and playing key roles in centrosome maturation, in the regulation of mitotic timing, and in building and stabilising the mitotic spindle (Nikonova et al, 2013). Nonetheless, it is now becoming increasingly clear that AURKA has several roles outside of mitosis, such as favouring neurite outgrowth (Mori et al, 2009), transcriptional activity through the MYC promoter (Zheng et al, 2016), and mitochondrial homeostasis (Bertolin et al, 2018;Grant et al, 2018). In this light, it is still unknown whether mitotic and non-mitotic functions of AURKA are made possible by a single, recycling pool of the kinase or by different pools at specific subcellular locations.…”
Section: Introductionmentioning
confidence: 99%